Evaluation of Dielectric Reliability in Oil-Insulated Transformers Using Scilab: Impact of Temperature and Electric Field Frequency - Maykop Pérez Martínez; Josnier Ramos Guardarrama (Revista Científica de Ingeniería Energética)
This article presents a study on the dielectric behavior of insulating oil in power transformers, using Scilab simulations as a primary tool. The research aims to analyze the impact of temperature, electric field frequency, and oil aging on dielectric properties like relative permittivity and dielectric strength. The study is crucial for transformers' operation and lifespan, as deteriorating dielectric properties can lead to failures and costly service interruptions. The study uses Scilab simulation to model and evaluate transformer insulation systems under different conditions, allowing for prediction of performance under different electrical stresses. The results provide valuable insights for transformer design, optimization, and diagnosis, contributing to a better understanding of insulating oil behavior. The findings also offer tools for developing more efficient equipment and implementing predictive maintenance strategies, ensuring continuity of electrical service and minimizing operational costs.